Sosialisasi Hukum Bahaya Narkoba Bagi Remaja SMK Negeri 2 Kota Tanjungbalai - Suriani Suriani; Cici Rahma Alia; Hikmah Ramadhani; Muhammad Fatwa Sitorus; Muhammad Idham (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Drugs are a challenge for the Indonesian people, especially the millennial generation or the generation of the nation's administrators, which can damage the mind, body and also the economy of anyone who uses them. So in this case, students care about the nation's generation. Drugs can also cause other people's bad actions, such as killing, stealing. , rape because the effects of drugs damage the mind. The purpose of this writing is to explain the dangers of drugs for teenagers because the number of drug users in Indonesia continues to increase and most of them are teenagers. Of the problems that have arisen today, many However, due to the many types of drug abuseIn the world of medicine, this is no longer used. This is a type of drug that is often abused and can cause dependence. There are various reasons why people use drugs, such as to relieve stress, have fun, or socialize with other people. The data analysis used was by analyzing various information collected from students of SMK Negeri 2 Tanjung Balai about the dangers of drugs, factors causing drug use among teenagers, and efforts to stop drug use. The results of this paper show that family factors that do not pay enough attention to children are the main cause of drug use by teenagers. To achieve this goal, this activity will use material delivery methods, discussions and question and answer sessions, as well as clinical services. The target of this activity is Tanjung Balai State Vocational School Students. The partner in this activity is TANJUNG BALAI Vocational School 2, considering that teenagers are the nation's generation and are easily influenced by drugs. After carrying out this activity, it is hoped that teenagers will be able to apply knowledge and abstain from using or abusing drugs and become a healthy generation, namely the golden Indonesian generation in 2045